(untitled) - Marquardt, Janet (Boston, 2003)
Frames of Reference develops students’ critical understanding and appreciation of art by focusing on interesting intersections among the viewpoints of patrons, artists, viewers, and critics. Thematically organized with a chronological underpinning, the text includes thought-provoking chapter topics such as "The Earth as Art," "Representations of the Gods," "Patrons and the Role of the Artist," "Utopia and Dystopia," and "Identity in Contemporary Art."
Keywords: Art; History